Measuring social housing dimensions: a case study of urban areas in Algeria - Djafri, Riadh; Mohamed Osman, Mariana (Emerald Publishing Limited, 2020)
Abstract Purpose – The purpose of this study is to develop a measurement model and measure the dimensions of Residential Quality and Housing Adequacy (RQHA), Social Housing Provision (SHP) and Residents’ Quality of Life (RQOL) by social housing residents in Batna city, Algeria. Design/methodology/approach – This study used a quantitative approach through the distribution of a self-administered questionnaire. A total of 373 useable questionnaires were collected from social housing residents in Batna city and used for the analysis. The data were analysed using descriptive statistics, exploratory factor analysis with principal component analysis through SPSS and confirmatory factor analysis usingAMOS. Findings – The measurement model revealed good fit of indices indicating that RQHA is presented by three sub-constructs, namely satisfaction with housing adequacy, satisfaction with current neighbourhood and satisfaction with housing design. In addition, the constructs of SHP and RQOL were measured by seven items each. The measurement model provides empirical evidence of the correlation between RQHA, SHP and RQOL constructs. Practical implications – The findings of this study contribute significantly to government, housing stakeholders, architects, project managers and urban planners in the context of social housing policymakers, design, planning and construction. The finding would be helpful to ameliorate housing quality, adequacy, provision and RQOL in terms of social housing scheme. Originality/value – This study identifies the correlation between constructs (RQHA, SHP and RQOL) and their dimensions in the context of social housing in Batna city by validating a measurement model using CFA.